Metagenomic insights into the microbial communities and functional traits of hot springs in Guizhou Province, China - Chen, Feng; Cheng, Min; Rong, Dongyun; Wang, Yanyan; Liang, Rubing; Irfan, Muhammad; Kang, Yingqian; Cao, Yu (Frontiers in Microbiology, 2025)
IntroductionHot springs were previously believed to be uninhabitable due to their hostile nature. However, recent studies have determined that hot springs not only have a rich microbiota but are also involved in various biogeochemical processes and possess unique characteristics that can be utilized for several biotechnological applications. This study aimed to determine the bacterial taxonomic diversity and functional profiles of 11 hot springs in the Guizhou Province, China.MethodsIllumina high-throughput sequencing was used to sequence the V3–V4 region of the 16S rRNA gene from microorganisms in samples collected from these hot springs. Software such as Mothur, the SILVA ribosomal RNA database, and Quantitative Insights into Microbial Ecology (QIIME) were utilized for taxonomic and operational taxonomic unit (OTU) analysis, while PICRUST2 was employed for functional predictions.ResultsGuizhou Baili Rhododendron Hot Spring No.1 (BLDJA) had the highest diversity in terms of species richness, while Jianhe Hot Spring (YAS) had the lowest diversity. At the phylum level, the highest reported phyla included Pseudomonadota, Bacillota, Nitrospirota, Bacteroidota, and Actinomycetota, where Pseudomonadota had the highest abundance (92.094%) in Jianhe Hot Spring (YAS) and the lowest (41.238%) in Guizhou Baili Rhododendron Hot Spring No. 2 (BLDJB). Bacillota has the highest abundance (39.178%) in Guizhou Baili Rhododendron Hot Spring No. 2 (BLDJB) and the lowest (0.547%) in Jiutian Hot Spring (SNJT). The highest predicted functions were observed for amino acid metabolism, followed by carbohydrates. Predicted pathways for secondary metabolite and vitamin synthesis, along with stress-adaptation genes, underscore the biotechnological value of these habitats.DiscussionThis study presents a preliminary survey of 11 hot springs in Guizhou Province, providing important insights into the origin and evolution of microorganisms. Furthermore, studying these microorganisms is crucial for understanding the adaptive mechanisms of life under extreme conditions, such as high temperatures, and for exploring the potential biotechnological applications of these microbes. An in-depth approach combining functional metagenomics and next-generation culturomics is required to fully understand the microbial flora and its potential biotechnological applications.